2010
DOI: 10.1007/bf03395737
|View full text |Cite
|
Sign up to set email alerts
|

Proactive and Preventive Coping in Adjustment to College

Abstract: differential exposure model of personality was borrowed to examine whether the students were exposed to different levels of current stress and to explore the impact of stress on maladjustment. The results suggest that stress has a mediating effect between proactive coping and maladjustment but not between preventive coping and maladjustment. The results also suggest that only proactive coping plays an important role in university adjustment, and proactive coping is a dispositional trait rather than a coping st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
(49 reference statements)
3
33
1
1
Order By: Relevance
“…And it is correlated with both preparing behavior and hunting behavior, which was suggested to positively influence the result of hunting, whereas preventive coping only correlated with preparing behavior. The findings were consistent with Gan et al (2007), who found that proactive coping, compared with preventative coping, had a significantly larger effect on student engagement and freshmen adjustment (Gan, Hu, & Zhang, 2010). However, Hypothesis 3, which proposed that both preventive coping and proactive coping were related to challenge appraisal, was not proved, which provoked us to reconsider the relationship between proactive coping and preventive coping.…”
Section: Future-oriented Coping and Job Huntingsupporting
confidence: 79%
“…And it is correlated with both preparing behavior and hunting behavior, which was suggested to positively influence the result of hunting, whereas preventive coping only correlated with preparing behavior. The findings were consistent with Gan et al (2007), who found that proactive coping, compared with preventative coping, had a significantly larger effect on student engagement and freshmen adjustment (Gan, Hu, & Zhang, 2010). However, Hypothesis 3, which proposed that both preventive coping and proactive coping were related to challenge appraisal, was not proved, which provoked us to reconsider the relationship between proactive coping and preventive coping.…”
Section: Future-oriented Coping and Job Huntingsupporting
confidence: 79%
“…Stress did not significantly predict educational adjustment; thus, low levels of stress were not positively related to better levels of adjustment. The results appear to be counterintuitive to those of Gan, Hu, and Zhang (2010), and Misra and Castillo (2004) who found that the first year of university was a stressful time due to the new educational and social challenges which students encounter.…”
Section: Discussioncontrasting
confidence: 51%
“…For many students, successful separation from parents and family and the establishment of emotional independence have a positive influence on educational adjustment (Lapsley, Rice, & Shadid, 1989;Hoffman, 1984). How they adjust to and cope with the educational and extracurricular demands of university life, including new and different responsibilities and challenges, is a critical factor in their academic success (Gan, Hu, & Zhang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…First-year students begin with the complex transition from adolescence to adulthood with different activities than before. Blimling & Miltenberger said when entering college, adjustments to campus life are one of the main transitions for students because they will face a college environment that was not known before [1]. Adjustment process with campus life can creates difficulties and affects to physical and psychological conditions and students who failed to achieve satisfaction in adjustment in college life will find many difficulties.…”
Section: Introductionmentioning
confidence: 99%